The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2024)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which species share a conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which mimicry is produced in poison frogs. We assembled a 6.02‐Gbp genome with a contig N50 of 310 Kbp, a scaffold N50 of 390 Kbp and 85% of expected tetrapod genes. We leveraged this genome to conduct gene expression analyses throughout development of four colour morphs of Ranitomeya imitator and two colour morphs from both R. fantastica and R. variabilis which R. imitator mimics. We identified a large number of pigmentation and patterning genes differentially expressed throughout development, many of them related to melanophores/melanin, iridophore development and guanine synthesis. We also identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species, and identify several plausible candidates for colouration in vertebrates (e.g. cd36 , ep‐cadherin and perlwapin ). Finally, we hypothesise that keratin genes (e.g. krt8 ) are important for producing different structural colours within these frogs.

Intraspecific divergence of sexual size dimorphism and reproductive strategies in a polytypic poison frog - Lia Schlippe Justicia; Martin Mayer; Ugo Lorioux-Chevalier; Carolin Dittrich; Bibiana Rojas; Mathieu Chouteau (Evolutionary Ecology, 2024)
Intraspecific variation in body size, both among populations and between sexes, is an important factor influencing life-history strategies. This variation might be the response to different environmental conditions, as well as natural and sexual selection, and can result in differences in behavior and reproductive strategies among populations. Here, we use the dyeing poison frog ( Dendrobates tinctorius ) as a model to investigate how interpopulation variation in body size and sexual size dimorphism affects reproductive strategies. As body size increased, sexual size dimorphism also increased, i.e., females were larger than males, and more so in populations with overall larger frogs. This indicates that there is a stronger selection for body size in females than in males, likely as a response to divergent reproductive investment between the sexes. Females from larger-bodied populations produced larger clutches, but the overall number of froglets produced per clutch did not differ among populations. We discuss potential causes and mechanisms that might be responsible for the observed divergence in body size, sexual size dimorphism, and reproductive strategies among populations that likely represent local adaptations. Our findings demonstrate the importance of cross-population studies, cautioning against drawing general conclusions about a species’ ecology without accounting for intraspecific variation.

RETRACTED: The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system - Adam M. M. Stuckert; Mathieu Chouteau; Melanie McClure; Troy M. LaPolice; Tyler Linderoth; Rasmus Nielsen; Kyle Summers; Matthew D. MacManes (Molecular Ecology, 2021)
A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which multiple species share the same conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which vivid colour and pattern are produced in a Müllerian mimicry complex of poison frogs. We did this by first assembling a high‐quality de novo genome assembly for the mimic poison frog Ranitomeya imitator . This assembled genome is 6.8 Gbp in size, with a contig N50 of 300 Kbp R . imitator and two colour morphs from both Ranitomeya fantastica and R . variabilis which R . imitator mimics. We identified a large number of pigmentation and patterning genes that are differentially expressed throughout development, many of them related to melanocyte development, melanin synthesis, iridophore development and guanine synthesis. Polytypic differences within species may be the result of differences in expression and/or timing of expression, whereas convergence for colour pattern between species does not appear to be due to the same changes in gene expression. In addition, we identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species. Finally, we hypothesize that genes in the keratin family are important for producing different structural colours within these frogs.

The development and characterization of polymorphic microsatellite loci for the genus Melinaea (Nymphalidae, Ithomiini) - Melanie McClure; Mathieu Chouteau; Bernard Angers; Marianne Elias (Conservation Genetics Resources, 2014)

The development and analysis of twenty-one microsatellite loci for three species of Amazonian poison frogs - Jason L. Brown; Mathieu Chouteau; Travis Glenn; Kyle Summers (Conservation Genetics Resources, 2009)